Unilateral Tuberculous Epididymo- Orchitis with Scrotal Fistula: a Case Report - Hosamirudsari, Hadiseh (Iran J Pathol, 2015)
Tuberculosis (TB) global prevalence remains almost unchanged over the past few decades. Though genitourinary tract tuberculosis is common, it is rarely associated with scrotal fistula. We present a rare case of advanced tuberculous epididymo-orchitis (TBEO) which culminated in removing the testis. Before final diagnosis is made, it was unresponsive to empirical therapy of bacterial epididymo-orchitis. The approaches to this case were clinical, radiological and histopatologic. For treatment and follow up see the case report.